Method of Prevent the for Years for a Change of Precision Punching Die - Tian Shaojie; Hu Zhongcheng; Liu Jing (Jixie chuandong)
The method and best heat treatment process to prevent the"for years for a change"of precision punching dies are presented. The method and parameters of heat treatment of dies are as follows. Firstly,after electric spark cutting,stress relief annealing of dies is used,which are heated to 650 ℃ and cooling in air furnace. Secondly,the dies are heated to 650 ℃ and 850 ℃ for pre- heating,then to 1 010 ℃ for quenching and the dies are cooled by pressed Nitrogen in vacuum furnace. Thirdly,the dies are deeply cooled to- 196 ℃,then,the tempering of dies is used which are heated to 250 ℃ for two times and following closely to 200 ℃ for one time. The production practice proved that after being treated by the above processes,the residual austenite of dies is decreased to 3%,the value of deformation is only 0. 000 8 mm. The result shows that,the dimension stability of dies is greatly increased and the life of dies is obviously prolonged.